MF59(®)‐adjuvanted vaccines for seasonal and pandemic influenza prophylaxis - Banzhoff, Angelika (Influenza Other Respir Viruses, 2008)
Abstract  Influenza is a major cause of worldwide morbidity and mortality through frequent seasonal epidemics and infrequent pandemics. Morbidity and mortality rates from seasonal influenza are highest in the most frail, such as the elderly, those with underlying chronic conditions and very young children. Antigenic mismatch between strains recommended for vaccine formulation and circulating viruses can further reduce vaccine efficacy in these populations. Seasonal influenza vaccines with enhanced, cross‐reactive immunogenicity are needed to address these problems and can confer a better immune protection, particularly in seasons were antigenic mismatch occurs. A related issue for vaccine development is the growing threat of pandemic influenza caused by H5N1 avian strains. Vaccines against strains with pandemic potential offer the best approach for reducing the potential impact of a pandemic. However, current non‐adjuvanted pre‐pandemic vaccines offer suboptimal immunogenicity against H5N1. For both seasonal and pre‐pandemic vaccines, the addition of adjuvants may be the best approach for providing enhanced cross‐reactive immunogenicity. MF59(®), the first oil‐in‐water emulsion licensed as an adjuvant for human use, can enhance vaccine immune responses through multiple mechanisms. A trivalent MF59‐adjuvanted seasonal influenza vaccine (Fluad(®)) has shown to induce significantly higher immune responses to influenza vaccination in the elderly, compared with non‐adjuvanted vaccines, and to provide cross‐reactive immunity against divergent influenza strains. Similar results have been generated with a MF59‐adjuvanted H5N1 pre‐pandemic vaccine, which showed higher and broader immunogenicity compared with non‐adjuvanted pre‐pandemic vaccines.